Prevalence of Achilles Tendinopathy among Recreational Badminton Players - MR.T.N. SURESH,; R. SHYLAJA,; SARA ASHMINA ASOKAN, (International Journal of Pharma and Bio Sciences, 2018)
Achilles tendinopathy is supposed to be a common type of injury suffered by almost all the recreational sports players, and predominantly by badminton players. Badminton is a well-played sport by both youngsters and adults. They keep playing until their point of exertion not realising the intensity of the injuries caused internally. This study aims to find the prevalence of Achilles tendinopathy amongst recreational badminton players such as college students and staff. An observational, non experimental study design was chosen. A convenient sample of 100 students was chosen from SRM University (where is it). The inclusion criteria was between 18 to 40 years of both genders. Exclusion criteria were recent surgery, fractures, hypercalcemia and other neurological problems. Based on the inclusion and exclusion criteria, 100 participants were selected and a questionnaire was given including Victorian Institute of Sports Assessment. The percentage of participants who were asymptomatic was 48% and those with symptoms of Achilles tendinopathy was 52%. From this study, it is concluded that the prevalence of Achilles tendinopathy among recreational badminton players is high.